The MAID - Prose, Nita (London, United Kingdom : Harpercollins Publishers, 2022)
THE HOTLY-ANTICIPATED DEBUT, COMING JANUARY 2022 I am your maid. I know so much about you. But when it comes down to it: what is it that you know about me? I am your maid. I know so much about you. But when it comes down to it: what is it that you know about me? Molly the Maid is all alone in the world. A nobody. She's used to being invisible in her job at the Regency Grand Hotel, plumping pillows and wiping away the grime, dust and secrets of the guests who pass through. She's just a lowly maid - why should anyone take notice? But Molly is thrown into the spotlight when she discovers an infamous wealthy guest, Mr Black, very dead in his bed. This isn't a mess that can be easily cleaned up. And so Molly becomes embroiled in a murder mystery hunt for the truth, learning who to trust as she navigates the dark underbelly of the Regency Grand. Escapist, charming, with a heroine as endearing as she is unreliable, THE MAID is a truly original story about how people are a mystery like no other, and how the truth isn't always black and white - it's often found in the dirtier, grey areas in between..
Keywords: v; Hotels -- Fiction; Murder -- Investigation -- Fiction